A secure and energy-efficient routing using coupled ensemble selection approach and optimal type-2 fuzzy logic in WSN - S. Ambareesh; Pundalik Chavan; S. Supreeth; Rajesh Nandalike; P. Dayananda; S. Rohith (Scientific Reports)
Abstract Wireless sensor networks (WSNs) are imperative to a huge range of packages, along with environmental monitoring, healthcare structures, army surveillance, and smart infrastructure, however they’re faced with numerous demanding situations that impede their functionality, including confined strength sources, routing inefficiencies, security vulnerabilities, excessive latency, and the important requirement to keep Quality of Service (QoS). Conventional strategies generally goal particular troubles, like strength optimization or improving QoS, frequently failing to provide a holistic answer that effectively balances more than one crucial elements concurrently. To deal with those challenges, we advocate a novel routing framework that is both steady and power-efficient, leveraging an Improved Type-2 Fuzzy Logic System (IT2FLS) optimized by means of the Reptile Search Algorithm (RSA). This modern framework employs weighted ensemble clustering and matched ensemble choice techniques, facilitating strong cluster formation and resulting in a substantial 98% development in community lifetime, an 80% enhancement in packet delivery ratio (PDR), and a 45% reduction in average power consumption while as compared to current protocols. The IT2FLS model dynamically adapts routing selections by means of assessing key parameters, consisting of dynamic accept as true with factors, node power ranges, course delays, and energy consumption fees, whilst the RSA algorithm exceptional-tunes the bushy common sense club features to make certain most beneficial cluster head choice and reliable multi-hop communication paths. Additionally, our proposed technique complements secure routing by means of efficaciously counteracting the effects of compromised nodes, for this reason maintaining community integrity. Multiple test results show that RSA’s enhanced IT2FLS system consistently outperforms new standards. It reduces end-to-end work by 25% and significantly increases productivity. These findings suggest that this robust routing model not only guarantees efficient data transmission and performance. But it also guarantees the stability of the overall network. This research contributes significantly to the WSN field by providing a comprehensive routing solution that integrates energy conservation, security, and QoS, ultimately extending the lifespan of WSNs and boosting confidence in critical applications, paving the way for implementation scenarios that require secure, low-power, and real-time data transmission.